ANALYSIS OF HRD AUDIT AND ITS IMPACT ON EMPLOYEE COMPETENCIES AND CAREER DEVELOPMENT IN AUTO-COMPONENTS INDUSTRY IN PUDUCHERRY (CAHIERS MAGELLANES-NS, 2024)
ABSTRACT: In the ever-evolving landscape of the Auto-components Industry in India, the effective management and development of human resources stand out as critical determinants of organizational success. The growth and innovation of the automotive sector depends on the capabilities of its workforce, making HRD practices central to organizational strategy. By exploring the outcomes of HRD audit in the Auto-components Industry in Puducherry, this study aims to uncover insights into the current state of human resource development, examining its alignment with industry benchmarks. This research focuses on the analysis of HRD audit and its impacts on employee competencies and career development within the specific context of the auto-components sector in Puducherry. The study employs an exploratory research methodology and adopts Mixed Research Approach, primarily relying on the collection of primary data through a structured questionnaire distributed to 125 employees in Auto-components companies in the Puducherry region, India. The research employs convenience sampling, a non-probability method, and utilizes both descriptive and inferential statistical tools for data analysis. The study showed that Managerial Employees have perceived more on the various HRD Audit Aspects, have perceived more Competencies and have more Career Development options in their organizations than their counter-part. The HRD Audit Aspects have strong, positive and high relationship with Employees’ Competencies and there is a high positive correlation between Employees’ Competencies and Career Development of employees. Out of various HRD Audit Aspects, ‘Succession Planning & Career Pathways’ has stronger influence and ‘Performance Management System’ Aspect has weaker influence and ‘Employee Engagement & Motivation’ Aspect has no significant influence on Career Development of employees in Auto-Components Industry. This study contributes to a deeper understanding of the relationship between HRD and employee dynamics, offering a foundation for further research and practical implications for organizations striving to thrive in the dynamic landscape of the Auto-Components Industry.